Pediatric Pulmonary Hemorrhage vs. Extrapulmonary Bleeding in the Differential Diagnosis of Hemoptysis - Michael Vaiman; Baruch Klin; Noa Rosenfeld; Ibrahim Abu-Kishk (University Library System, University of Pittsburgh, 2017)
Introduction: Hemoptysis is an important symptom which causes a major concern, and warrants immediate diagnostic attention. The authors compared a group of patients with pediatric pulmonary hemorrhage with pediatric patients diagnosed with extrapulmonary bleeding focusing on differences in etiology, outcome and differential diagnosis of hemoptysis. Methods: We performed the retrospective analysis of medical charts of 134 pediatric patients admitted to the Emergency Department because of pulmonary and extrapulmonary hemorrhage and were diagnosed with suspected hemoptysis or developed hemoptysis (ICD10-CM code R04.2). The cases with pulmonary hemorrhage (Group 1) were compared with cases of extrapulmonary bleeding (Group 2) using the Fisher Exact test or Pearson's χ2 test for categorical variables. The t-test was used to assess differences between continuous variables of the patients in the two groups. Results: Bloody cough was the presenting symptom in 73.9% of cases. 30 patients had pulmonary hemorrhage (Group 1), while 104 patients had extrapulmonary bleeding (Group 2). The underlying causes of bleeding in Group 2 included epistaxis, inflammatory diseases of nasopharynx and larynx, foreign bodies, gingivitis, and hypertrophy of adenoids. Mortality rate was 10% in Group 1, whereas Group 2 did not have any mortality outcomes during the observation period. Etiologycal factors were significantly different between hemoptysis and extrapulmonary bleeding in children Conclusions: Our research suggested that pulmonary and extrapulmonary bleeding are two conditions that differ significantly and cannot be unified under one diagnostic code. It is important to differentiate between focal and diffuse cases, and between pulmonary and extrapulmonary hemorrhage due to the diversity of clinical courses and outcomes.